2021
DOI: 10.1002/cam4.4330
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of driver mutations from cytological samples and cfDNA in lung cancer

Abstract: Background Bronchoscopy is a minimally invasive procedure for establishing the diagnosis of lung cancer. It sometimes fails to obtain tissue samples but readily collects cytological samples. Methods We developed PNA‐LNA dual‐PCR (PLDP), which amplified mutant sequences by a high‐fidelity DNA polymerase in the presence of a peptide nucleic acid (PNA) oligomer having a wild‐type sequence. Mutations are detected either by locked nucleic acid (LNA) probes for quick detection of a limited number of mutations, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…World-wide screenings reported an intrinsic T790M frequency ranging ~3-80% [248][249][250][251][252][253], that was attributed to potential sequencing artifacts caused by tissue processing [254]. In a paired experiment, comparing mass spectrometry with standard direct sequencing, the frequency of T790M shifted from 31.5% to 2.7% [255], implying detection methods must be carefully standardized.…”
Section: Egfr-dependent Mechanisms Of Resistancementioning
confidence: 99%
“…World-wide screenings reported an intrinsic T790M frequency ranging ~3-80% [248][249][250][251][252][253], that was attributed to potential sequencing artifacts caused by tissue processing [254]. In a paired experiment, comparing mass spectrometry with standard direct sequencing, the frequency of T790M shifted from 31.5% to 2.7% [255], implying detection methods must be carefully standardized.…”
Section: Egfr-dependent Mechanisms Of Resistancementioning
confidence: 99%
“…In respect of the use of cytological material, several authors have detected BRAF mutations in cytological samples by PCR-based methods. 64,65 Kaya et al observed an adequacy rate of 100% for BRAF testing in EBUS-TBNA specimens. 66 However, other authors have reported lower adequacy rates for BRAF analysis.…”
Section: Brafmentioning
confidence: 99%
“…However, these assays do not detect rare mutations, which may influence treatment response. In respect of the use of cytological material, several authors have detected BRAF mutations in cytological samples by PCR‐based methods 64,65 . Kaya et al observed an adequacy rate of 100% for BRAF testing in EBUS‐TBNA specimens 66 .…”
Section: Molecular Markers In Lung Nsclcmentioning
confidence: 99%